1990
DOI: 10.1111/j.1439-037x.1990.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Plant Water Stress on Net Photosynthesis and Yield of Sunflower (Helianthus annuus L.)

Abstract: The effect of plant water stress on net photosynthesis, leaf growth, yield and yield‐related components were investigated in a single experiment in order to determine in which way water deficits affect sunflower yields. Sunflower plants, grown under controlled temperature regimes, were stressed during budding, anthesis and seed filling by withholding water until the leaf water potential reached ‐1600 and ‐2000 kPa. Leaf area of unstressed plants significantly exceeded that of plants under severe stress during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…Boyer et al (1980) found that soybean plants with ample water supplies can experience water deficits due to high transpiration rates. Further, Human et al (1990) stated that, when sunflower plants were grown under controlled temperature regimes, water stress during budding, anthesis and seed filling, the CO 2 uptake rate per unit leaf area as well as total uptake rate per plant significantly diminished with stress, while this effect resulted in a significant decrease in yield per plant. The correlation between climatic factors and both boll production and boll retention over sets of 15 d periods after flowering (boll setting) day (Tables 5 & 6) revealed the following in Season I.…”
Section: Correlation Estimatesmentioning
confidence: 99%
“…Boyer et al (1980) found that soybean plants with ample water supplies can experience water deficits due to high transpiration rates. Further, Human et al (1990) stated that, when sunflower plants were grown under controlled temperature regimes, water stress during budding, anthesis and seed filling, the CO 2 uptake rate per unit leaf area as well as total uptake rate per plant significantly diminished with stress, while this effect resulted in a significant decrease in yield per plant. The correlation between climatic factors and both boll production and boll retention over sets of 15 d periods after flowering (boll setting) day (Tables 5 & 6) revealed the following in Season I.…”
Section: Correlation Estimatesmentioning
confidence: 99%
“…The soil texture was a clay loam, with an alluvial substratum (pH = 8.07, 42.13% clay, 27.35% silt, 22.54% fine sand, 3.22% coarse sand, 2.94% calcium carbonate and 1.70% organic matter) [14].…”
Section: Methodsmentioning
confidence: 99%
“…In season I, the field was irrigated on 15 March (at planting), 8 April (first irrigation), 29 April, 17 May, 31 May, 14 June, 1 July, 16 July, and 12 August. In season II, the field was irrigated on 23 March (planting date), 20 April (first irrigation), 8 May, 22 May, 1 June, 18 June, 3 July, 20 July, 7 August and 28 August. Techniques normally used for growing cotton in Egypt were followed.…”
Section: Methodsmentioning
confidence: 99%
“…Water deficits during seed formation and seed filling period have shown to cause significant reduction in number of seeds (achene) per capitulum (Daulay andSingh, 1983 andHuman et al, 1990). Babu et al (1993) reported that, scheduling of irrigation at 60 mm and 80 mm CPE produced significantly more number of filled seeds capitulum -1 as compared to irrigations at 100 mm CPE and at critical stages.…”
mentioning
confidence: 99%